Conversor CC-CA para painéis fotovoltaicos com conceito de filtragem ativa para redução da capacitância do barramento CC - Bezerra, Marcus Anderson Almeida (2016)
This work has as objective the project a single phase inverter for photovoltaic panels in the kilowatt scale to be connected to the electrical grid, following specifications of The Little Box Challenge, adopting a topology to improve efficiency, provide an injected current with a minimum harmonic distortion as possible and reduce the leakage current. Furthermore, it was sought the development of alternatives to rising the inverter power density, adopting an active filtering technique to eliminate the low frequency ripple coming from the DC-AC conversion. Thus, reducing the transferred energy to the DC source without the need of a high impedance, which implies in the reduction of cost and of total volume of the capacitive bank. On the inverter it is used a resonant control technique and a LC filter configuration in the output to dissociate from the AC side in the moment of null voltage and provide a current in phase with the grid voltage with low harmonic content. The validation of the topology is adopted performed through simulations and tested experimentally in the laboratory by a 2kW prototype